2023
DOI: 10.1093/nar/gkad253
|View full text |Cite
|
Sign up to set email alerts
|

TheEscherichia coliFur pan-regulon has few conserved but many unique regulatory targets

Abstract: While global transcription factors (TFs) have been studied extensively in Escherichia coli model strains, conservation and diversity in TF regulation between strains is still unknown. Here we use a combination of ChIP-exo–to define ferric uptake regulator (Fur) binding sites–and differential gene expression–to define the Fur regulon in nine E. coli strains. We then define a pan-regulon consisting of 469 target genes that includes all Fur target genes in all nine strains. The pan-regulon is then divided into th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 64 publications
1
2
0
Order By: Relevance
“…2A ). Furthermore, that same study ( 33 ) showed Fur does not directly bind the fliC promoter, a result corroborated by several other studies ( 25 , 26 ). We also analyzed the upstream intergenic region of fliC using the bioinformatics tool BPROM (Softberry.com), which did not uncover any putative fur boxes.…”
Section: Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…2A ). Furthermore, that same study ( 33 ) showed Fur does not directly bind the fliC promoter, a result corroborated by several other studies ( 25 , 26 ). We also analyzed the upstream intergenic region of fliC using the bioinformatics tool BPROM (Softberry.com), which did not uncover any putative fur boxes.…”
Section: Resultssupporting
confidence: 81%
“…This phenotype corresponded with an increase in flagellin transcript, protein, and surface expression of flagella. Knowing that the well-studied Fur regulator was likely not facilitating this regulation in our tested conditions ( 25 , 26 ), we took a forward genetic screening approach to identify the mediator of the iron-restricted enhanced motility phenotype. Through systematic deletion of regulatory genes, we ultimately found that deletion of the gene encoding dihydrolipoyl dehydrogenase, lpdA , led to a loss of iron-mediated motility as well as fitness in vivo .…”
Section: Introductionmentioning
confidence: 99%
“…The ferric uptake regulator (Fur) is the founding member of the Fur superfamily that regulates intracellular metal homeostasis in bacteria ( 1 , 2 ). In Escherichia coli , Fur regulates over 158 genes ( 3 , 4 , 5 ) involved in intracellular iron homeostasis, energy metabolism, DNA synthesis, oxidative stress response, and bacterial virulence ( 6 , 7 ). In the past 3 decades, it was postulated that when intracellular free iron content is elevated, Fur binds its corepressor a mononuclear ferrous iron ( 1 , 2 , 8 , 9 ) and regulates the expression of its target genes by binding to a specific DNA sequence known as the Fur-box ( 10 , 11 , 12 ).…”
mentioning
confidence: 99%